A New Destination of Online Travel Business: A Case Study. Issue 2 (June 2019) - Mahapatra, Durga Madhab; Patra, Soumendra Kumar
Technology is the lifeblood of the online travel business. Over the last two years, mobile has proved to be the biggest game changer. The possibilities and scalability of business are faster with cloud. Further, the Indian online hotel industry was expected to be USD1.8 billion by 2016 which was USD0.8 billion in the year 2015. India is among the top five traffic sources for 'trip advisor' globally. These are early days for online booking in India. India's biggest online travel firms are seeking to dominate hotel bookings as the industry ventures beyond low-margin airline ticketing. The companies like MakeMyTrip and Goibibo have been offering cheap flight tickets and travel packages. The digital revolution in India, driven by the roll-out of 4G, reducing costs, increasing smartphone penetration and increasing time spent on mobile phones will ensure that digital architecture will also grow at a faster clip compared to traditional media. Thus, the growth of digital advertising during 2017 (`82.02 billion), 2018 (`108.51 billion), 2019 (`143.54 billion) and 2020 (`189.86 billion) as per Dentsu Aegis Network. Online travel portal MakeMyTrip has formed a partnership with Flipkart to allow consumers to book domestic flights tickets and other travel services directly through the e-commerce firm's portal.